Performance assessment of the Greater Tehran Area buried gas distribution pipeline network under liquefaction. Issue 124 (September 2019) - Nourzadeh, Dan (Danesh); Mortazavi, Pedram; Ghalandarzadeh, Abbas; Takada, Shiro; Ahmadi, Mohammad
Abstract: The interconnectedness of current urban life with infrastructures urges the decision-makers to consider the resilience of urban lifeline systems as a priority. This motivates the research presented here, where the performance of a complex urban gas distribution system in a city with more than 12 million resident population is evaluated under the effects of seismic-induced liquefaction. The paper reviews the liquefaction potential in the Greater Tehran Area, and identifies the inputs for the analysis of soil-pipe interactions. The performance assessment is carried out using both numerical (finite elements analysis) and small scaled experimental assessments, for validation of the numerical models. The experimental results indicate that the numerical models are adequate for the performance evaluation of buried pipelines. The assessment shows that the buried pipelines perform well in most areas of the city, however, structural damage is expected in areas with higher seismic demands. In such areas, hands-on countermeasures are proposed to mitigate the risk of liquefaction-induced damage on the buried pipelines system. The results, methodology and procedures can be used as a framework the similar urban infrastructure risk analysis and mitigation studies. Highlights: Liquefaction potential methodologies in urban areas are reviewed, along with the past studies in the studied region in the Greater Tehran Area. The main inputs in soil-pipe analysis, such as characteristics of the pipe, surrounding soil and the permanent ground displacements (PGDs) are gathered. Effects of the liquefaction-induced PGDs on the buried gas pipelines are analysed using finite element analysis (FEA) verified against experimental studies in shaking table test facilities. The risk assessment and risk mitigation counter-measures are presented to improve the response of the buried pipeline systems in the area. Methodology, results and procedures can be very useful in the similar research and case-studies.